Problem-Based Tasks in Mathematics Learning: Opportunities and Challenges for Teachers - Suryanti, Sri; Nusantara, Toto; Parta, I Nengah; Irawati, Santi (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Mathematics education and teaching should not only include routine tasks; but tasks that need practice and memorization are mathematically more prosperous and more difficult because they promote problem-solving, investigation, and the discovery of the actual value of mathematical assertions. Therefore, the teacher must be able to select, create, and modify assignments under the established goals. This study attempts to examine opportunities and challenges that teachers encounter while adopting problem-based tasks. The subjects involved in this study were three secondary school mathematics teachers that are acceptable, in East Java, Indonesia. The teachers involved have more than five years of teaching experience and have good academic qualifications. The data collection consisted of observing three classes of secondary school during the implementation of a problem-based task related to the topic of rectangles and algebra. The study begins with the introduction and giving of several examples of problem-based tasks in secondary school mathematics designed to foster advanced learners' critical thinking and creativity. The findings show that teachers gain new knowledge about problem-based assignments and pedagogical insights on how they explain them to students. The results also provide an overview of the challenges for teachers to design and implement problem-based tasks.